Legacies from the 28th Winter Universiade in Almaty Kazakhstan. A case study of Mega-sport and Cultural Events - Tyo, Yelena (Πανεπιστήμιο Πελοποννήσου, 2021)
The study of mega-events and their legacies has gained popularity among researchers in recent years. As discussed later in this thesis, mega-events have four different types of impacts: social, economic, physical, and environmental. Some of the impacts, like physical, can have a long-term effect and thereby become a legacy of an event. The purpose of this study is to demonstrate the legacies of the 28th Winter Universiade and determine whether they are beneficial for the host city, region or country. The qualitative research method was selected for this study, which has created some limitations. The interviews were conducted with the residents of the host city Almaty and interviewsof foreign athletes were collected from secondary sources to generate the data for analysis. The work of Maguire and Delahunt (2017) on thematic analysis was used as the basis of the methodology in this study. The primary data collected from the interviews with the residents of the host city was translated from Russian into English. The findings revealed that the overall residents’ perception of hosting the 28th Winter Universiade was positive, argued by the benefits that the event has provided. Foreign athletes shared the same opinion with the residents about the event and the hosting of it.
Keywords: Φιλοξενία αθλητικών εκδηλώσεων; Αθλητισμός - Οικονομικές απόψεις; Ολυμπιακοί αγώνες - Οικονομικές απόψεις; Ολυμπιακοί αγώνες - Κοινωνικές απόψεις; Αθλητισμός και τουρισμός; Hosting of sporting events; Sports - Economic aspects; Olympics - Economic aspects; Olympics - Social aspects; Sports and tourism; Mega-Event; Mega-Sporting Event; Winter Universiade; Sporting Legacy